The scope of flavin-dependent reactions and processes in the model plant Arabidopsis thaliana. (September 2021) - Eggers, Reinmar; Jammer, Alexandra; Jha, Shalinee; Kerschbaumer, Bianca; Lahham, Majd; Strandback, Emilia; Toplak, Marina; Wallner, Silvia; Winkler, Andreas; Macheroux, Peter
Abstract: Flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD) are utilized as coenzymes in many biochemical reduction-oxidation reactions owing to the ability of the tricyclic isoalloxazine ring system to employ the oxidized, radical and reduced state. We have analyzed the genome of Arabidopsis thaliana to establish an inventory of genes encoding flavin-dependent enzymes (flavoenzymes) as a basis to explore the range of flavin-dependent biochemical reactions that occur in this model plant. Expectedly, flavoenzymes catalyze many pivotal reactions in primary catabolism, which are connected to the degradation of basic metabolites, such as fatty and amino acids as well as carbohydrates and purines. On the other hand, flavoenzymes play diverse roles in anabolic reactions most notably the biosynthesis of amino acids as well as the biosynthesis of pyrimidines and sterols. Importantly, the role of flavoenzymes goes much beyond these basic reactions and extends into pathways that are equally crucial for plant life, for example the production of natural products. In this context, we outline the participation of flavoenzymes in the biosynthesis and maintenance of cofactors, coenzymes and accessory plant pigments ( e. g. carotenoids) as well as phytohormones. Moreover, several multigene families have emerged as important components of plant immunity, for example the family of berberine bridge enzyme-like enzymes, flavin-dependent monooxygenases and NADPH oxidases. Furthermore, the versatility of flavoenzymes is highlighted by their role in reactions leading to tRNA-modifications, chromatin regulation and cellular redox homeostasis. The favorable photochemical properties of the flavin chromophore are exploited by photoreceptors to govern crucial processes of plant adaptation and development. Finally, a sequence- and structure-based approach was undertaken to gain insight into the catalytic role of uncharacterized flavoenzymes indicating their involvement in unknown biochemical reactions and pathways in A. thaliana . Graphical abstract: Image 1 Highlights: 262 genes encode flavoproteins accounting for 0.93% of the protein coding regions. The genome harbors a remarkable number of multigene families of flavoenzymes. Flavoenzymes are crucial for plant-specific reactions in secondary metabolism. Flavoproteins play central roles in processes regulated by blue light. As many as 37 putative flavoenzymes are involved in unknown reactions.